Allegorical Conjectures in Helon Habila’s Measuring Time - Anasiudu, Okwudiri (Research in African literatures, 2025)
Allegory, from the classical and medieval traditions, has been used to explore universal themes with specific texts seen as allegorical works. In recent scholarship, it has come under critique for the centering and one-dimensional view from which scholars explore it, which privileges Eurocentric biases and lacks the context specificity needed to address the unique challenges of peripheral spaces in the aftermath of colonization. This gap has engendered a growing advocacy for a form of allegoresis that decenters dominant narratives and incorporates marginalized perspectives. In this paper, my focus on allegoresis aims to uncover the allegorical layers of a text, drawing on postcolonial theory, particularly Stephen Slemon’s concept of postcolonial allegory, in my analysis of Helon Habila’s Measuring Time . This dimension has been overlooked in existing literary scholarship on the novel. Specifically, I map three types of allegorical conjectures in the novel, the allegoresis of unmasking and subversion, of departure/return and war, and of counter-discursivity. Through this exploration, I contribute to a deeper understanding of how reading allegory in a postcolonial text can open new insights into the texts as a site for cultural resistance.